2002
DOI: 10.1046/j.1365-2745.2002.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ozone and nitrogen dioxide on the permeability of bronchial epithelial cell cultures of non‐asthmatic and asthmatic subjects

Abstract: These results suggest that HBECs of asthmatics may be more susceptible to the deleterious effects of these pollutants. Whether in patients with asthma the greater susceptibility of bronchial epithelial cells to O3 and NO2 contributes to the development of the disease, or is a secondary characteristic of this condition, remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…Such changes have been seen to correspond to an increase in ionic and macromolecular permeability (Xiao et al, 2011;Bai et al, 2015;Freishtat et al, 2011;Watson et al, 2010). It has also been shown that the permeability of the bronchial epithelial cell layer is only increased in asthmatic subjects after exposure to ozone or nitrogen dioxide (Bayram et al, 2002), and that mediator release is altered after exposure of ALI cultures from asthmatic donors to respiratory syncytial virus (RSV) or particulate matter (Hackett et al, 2011b). Using cells derived from patients with COPD, ALI cultures show higher baseline levels of cytokine expression and increased susceptibility to RSV infection, despite an increased IFN response tem is specially designed for direct contact between cells and components of the test atmosphere at the air/liquid interface.…”
Section: Fully Differentiated 3d Human Airway Epithelial Modelsmentioning
confidence: 97%
“…Such changes have been seen to correspond to an increase in ionic and macromolecular permeability (Xiao et al, 2011;Bai et al, 2015;Freishtat et al, 2011;Watson et al, 2010). It has also been shown that the permeability of the bronchial epithelial cell layer is only increased in asthmatic subjects after exposure to ozone or nitrogen dioxide (Bayram et al, 2002), and that mediator release is altered after exposure of ALI cultures from asthmatic donors to respiratory syncytial virus (RSV) or particulate matter (Hackett et al, 2011b). Using cells derived from patients with COPD, ALI cultures show higher baseline levels of cytokine expression and increased susceptibility to RSV infection, despite an increased IFN response tem is specially designed for direct contact between cells and components of the test atmosphere at the air/liquid interface.…”
Section: Fully Differentiated 3d Human Airway Epithelial Modelsmentioning
confidence: 97%
“…60 Using animal or in vitro models, NO 2 produces eosinophilic inflammation, enhances epithelial damage, reduces mucin expression and increases baseline smooth muscle tone. [60][61][62][63] Repeated exposure to high doses of NO 2 is associated with increased breath frequency and decreased lung distensibility and gas exchange. 64 It has also been explained that NO 2 decreases bactericidal activity and alveolar macrophage activity.…”
Section: Mechanismsmentioning
confidence: 99%
“…For example, TNF-α has been shown to alter epithelial cell permeability, as well as to stimulate IL-6, IL-8 and GM-CSF expression [3]. A number of studies have shown that the epithelium of patients who have airway inflammatory diseases is structurally and functionally altered [4][5][6][7], and that bronchial epithelial cells that are isolated from patients with asthma or cystic fibrosis (CF) express increased levels of cytokines [1,3]. Therefore, it is important to fully understand gene regulation in airway epithelium in order to alleviate airway inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%